Dynamic Change of VOR and Otolith Function in Intratympanic Gentamicin Treatment for Ménière’s Disease: Case Report and Review of the Literature - L. E. Walther; R. Huelse; K. Blättner; M. B. Bloching; A. Blödow (Case Reports in Otolaryngology)
Intratympanic gentamicin treatment (IGT) is an evidence-based therapeutic option for recurrent vertigo attacks in Ménière’s disease (MD). Today, in MD it is possible to monitor changes of vestibular receptor function, induced by IGT, with objective test methods such as the video head impulse test (vHIT) and cervical and ocular vestibular evoked myogenic potentials (cVEMP, oVEMP) in a dynamic, time-and frequency-dependent manner. We report on a 65-year-old female patient with recurrent vertigo attacks in a right-sided MD, where receptor function was followed up before and up to 4 weeks after IGT (time dynamic). Quantitative changes of vestibular function (frequency dynamic) were detected with bithermal calorics and vHIT, with air-conducted sound (ACS) cVEMP and bone-conducted vibration (BCV) oVEMP at 500 Hz. The horizontal vestibuloocular reflex (hVOR) gain in vHIT decreased successively until the 4th week with the appearance of catch-up covert and catch-up overt refixation saccades, and side asymmetry increased in caloric testing. Saccular function was extinguished within 4 weeks, whereas utricular function was diminished after 4 weeks. Monitoring vestibular receptor function with objective test methods provides a quantitative insight into the dynamic activity of vestibular function and is therefore applicable in order to adjust IGT regimen at different therapeutic stages.